Psychopathological networks in cognitive-behavioral treatments for binge-eating disorder - Hilbert, Anja; Herpertz, Stephan; Zipfel, Stephan; Tuschen-Caffier, Brunna; Friederich, Hans-Christoph; Mayr, Andreas; Zwaan, Martina de (Psychotherapy and psychosomatics, 2020)
Introduction: Network approaches to psychopathology posit that mental disorders emerge from interrelated symptoms, and thus connectivity among symptoms are assumed to negatively predict the treatment response and decrease with efficacious treatment. Objective: This study uniquely sought to elucidate the network structure, its change, and its predictive value in cognitive-behavioral therapy (CBT) for binge-eating disorder (BED). Methods: In a multicenter randomized trial of face-to-face and Internet-based guided self-help CBT, 178 individuals with full syndrome and subsyndromal BED, eating disorder and general psychopathology, and body mass index (BMI) were subjected to Gaussian Graphical Network and Exploratory Graph Analyses before and after treatment and at 6-month follow-up. Results: At pretreatment, 3 network communities of: eating disorder psychopathology; general psychopathology; and restraint and BMI were identified, with the latter community included in the first thereafter. Eating disorder-related impairment and self-esteem were the most central symptoms, while BMI and binge eating had the lowest centrality. Network connectivity significantly increased from pre- to posttreatment, with the greatest increases in strength centrality found in binge eating and shape concern, but it did not predict remission from binge eating. Conclusions: With decreasing symptom severity, CBT resulted in a greater integration and connectivity of the psychopathology network in BED, suggesting an increased patient understanding of relations between binge eating and other symptoms. Network connectivity was not a negative prognostic indicator of treatment outcome. These results indicate a need for further research on the predictive value of network variables in the explanation of therapeutic change for patients with BED.
Gesehen am 26.11.2020